RF shielding for multi-copter based electromagnetic metrology platforms - Pienaar, H.; Andriambeloson, J.; Davidson, David (2017)
© 2016 IEEE. Radio frequency (RF) metrology using unmanned aerial vehicles (UAV's) is adding a new dimension to Electromagnetic Compatibility (EMC) investigations. However, the self-induced radio frequency interference (RFI) has limited its applications. We investigate the feasibility of an RFI-quiet multicopter, designed from inception with electromagnetic shielding in mind. This work discusses and tests the shielding effectiveness (SE) of the designed vehicle. Shielding levels between 20-30 dB were obtained without adding significant weight to the vehicle. This effort reduced the total radiated RFI power to -70 dBm with possible future improvements further reducing this level to below our measurement noise floor.